The puzzle of falling happiness despite rising income in rural China: ten hypotheses - Knight, J; Ma, B; Gunatilaka, R (University of Oxford, 2020)
With economic development can come social, attitudinal and cultural change, for good or ill or both We pose an unexplored question: why has happiness fallen in rural China whereas rural income has risen rapidly? Two rich data sets are analysed, the rural surveys of the China Household Income Project (CHIP) relating to 2002 and 2013. Our main methods are happiness regressions and decomposition methodology. Several approaches are adopted and no fewer than ten hypotheses are tested. One approach is to examine the variables that are found to be important in happiness functions and to consider their contributions to the fall in the mean happiness score of rural people. Three variables stand out and together can ‘explain’ over twice the fall in happiness: reduced sensitivity of happiness to income, increased sensitivity of happiness to relative income position in the village, and a sharper U-shape of happiness in response to ageing. Another approach is to analyse the effect on rural happiness of the vast rural-urban migration that took place over this period, in particular the effect of temporary migration on information flows to the village, thus broadening reference groups and changing attitudes, and its effect on the lives of those ‘left-behind’ in unbalanced households. This is followed up by introducing tests of the role that changing attitudes – towards sense of community, degree of materialism, and aspirations for income - might have played. The analysis is illuminating both substantively and methodologically, but a puzzle remains. A general conclusion is that the effects of development-driven social change on happiness both directly and also indirectly through changing attitudes are good candidates for further research.